Land Use Land Cover and Population Changes in Bhaktapur District - Prajapati, Raghu Nath (Journal of Advanced Academic Research, 2024)
Bhaktapur District, renowned for its cultural heritage, has undergone substantial land use and population changes from 2001 to 2019 and 2001 to 2021, respectively, driven by rapid urbanization and economic growth. This study employs Geographic Information System (GIS) tools and demographic data from the Central Bureau of Statistics (CBS) to examine these changes. Findings highlight a significant rise in built-up areas, especially around Bhaktapur city and neighboring municipalities like Madhyapur Thimi and Suryabinayak, which has led to a notable decrease in agricultural land. Specifically, built-up areas expanded by 5.56 m² in Changunarayan from 2001 to 2011 and by 4.155 m² in Suryabinayak from 2011 to 2019. While forested areas remained stable until 2011, they saw a substantial decline, notably a decrease of 21.683 m² in Madhyapur. Cropland has also diminished across all municipalities, with Changunarayan and Madhyapur experiencing the highest reductions of 36.89 m² and 33.23 m², respectively. Population growth has been particularly pronounced in Madhyapur and Suryabinayak, with Madhyapur experiencing a 5.8% increase in 2011 and Suryabinayak a 5.7% increase in 2021, whereas Bhaktapur city saw a slight decrease. These trends emphasize the impact of urban expansion on agricultural land and highlight the necessity for strategic urban planning. The study advocates for sustainable development practices that reconcile urban growth with the preservation of agricultural land and natural resources. It urges policymakers and urban planners to implement strategies that safeguard remaining farmland, promote sustainable urban agriculture, and protect the district’s cultural and environmental assets for long-term ecological and economic stability.